Assessment of morbidity and mortality by influenza A (H1N1) among pregnant women in Western Rajasthan, India - Dr.R.S.Parihar4 , Dr.P.K.Khatri5, Dr. Ramesh Agrawal1 , Dr.Vinod K.Maurya2 Dr.Kanhaiya lal seervi3; Dr. Archna Bora7, Dr.Saroj Meena6 , (International Journal of Scientific Research and Management (IJSRM), 2017)
Background: Influenza has a major impact on public heath, First outbreak of influenza as a pandemicdeclared by WHO in June 2009. The present study determines the morbidity and mortality of influenza A(H1N1) by real time reverse transcriptase polymerase chain reaction (RT-PCR) method in pregnant women.Objective: To study the morbidity and mortality of influenza A (H1N1) by RT-PCR Method in pregnantwomen.Materials and Methods: 702 respiratory samples (nasopharyngeal swabs) of reproductive age group (17 to 45yrs) women were collected from Dr S. N. Medical College & associated group of Hospitals from January 2015to March 2015. The samples were collected and processed as per World Health Organization (WHO)guidelines. Viral RNA was extracted and one-step RT-PCR was performed to detect influenza A (H1 and N1)virus.Results: Out of 702 samples 230 (32.7%) were pregnant and 472 (67.3%) were non pregnant women. Amongpregnant 63 (27.4%) and among non pregnant 120 (25.4%) were positive for influenza A (H1N1) and 18(28.5%) pregnant women died due to influenza A (H1N1) infections.Conclusion: It was observed that influenza A (H1N1) was prevalent in pregnant women in western Rajasthan(Jodhpur). We emphasize on early detection and monitoring of influenza in pregnant women which will behelpful in patient management who are at risk for influenza complications.